Fe-Catalyzed dicarbofunctionalization of electron-rich alkenes with Grignard reagents and (fluoro)alkyl halides. Issue 93 (9th November 2021) - Rotella, Madeline E.; Sar, Dinabandhu; Liu, Lei; Gutierrez, Osvaldo
Abstract : A three-component iron-bisphosphine-catalyzed regioselective dicarbofunctionalization of electron-rich alkenes is described. Abstract : An iron-catalyzed regioselective dicarbofunctionalization of electron-rich alkenes is described. In particular, aryl- and alkyl vinyl ethers are used as effective linchpins to couple alkyl or (fluoro)alkyl halides and sp 2 -hybridized Grignard nucleophiles. Preliminary results demonstrate the ability to engage thioethers as linchpins and control enantioselectivity in these transformations, an area which is largely unexplored in iron-catalyzed three-component cross-coupling reactions.